Modeling neural development - Van Ooyen, Arjen (Developmental cognitive neuroscience., 2003)
Studies neural development using computational and mathematical modeling. Modeling provides precise and exact ways of expression, which allow us to go beyond the insights that intuitive or commonsense reasoning alone can yield. Most neural modeling focuses on information processing in the adult nervous system. This book shows how models can be used to study the development of the nervous system at different levels of organization and at different phases of development, from molecule to system and from neurulation to cognition.